Molecular Detection of Persistent Francisella tularensis Subspecies holarctica in Natural Waters - T. Broman; J. Thelaus; A.-C. Andersson; S. Bäckman; P. Wikström; E. Larsson; M. Granberg; L. Karlsson; E. Bäck; H. Eliasson; R. Mattsson; A. Sjöstedt; et al. (International Journal of Microbiology)
Tularemia, caused by the bacterium Francisella tularensis, where F. tularensis subspecies holarctica has long been the cause of endemic disease in parts of northern Sweden. Despite this, our understanding of the natural life-cycle of the organism is still limited. During three years, we collected surface water samples (n=341) and sediment samples (n=245) in two areas in Sweden with endemic tularemia. Real-time PCR screening demonstrated the presence of F. tularenis lpnA sequences in 108 (32%) and 48 (20%) of the samples, respectively. The 16S rRNA sequences from those samples all grouped to the species F. tularensis. Analysis of the FtM19InDel region of lpnA-positive samples from selected sampling points confirmed the presence of F. tularensis subspecies holarctica-specific sequences. These sequences were detected in water sampled during both outbreak and nonoutbreak years. Our results indicate that diverse F. tularensis-like organisms, including F. tularensis subsp. holarctica, persist in natural waters and sediments in the investigated areas with endemic tularemia.